New geochronological and provenance constraints on the Late Mesozoic sedimentary formations in the western Shandong Province and Tanlu fault zone, China - Meng, Yuanku; Yuan, Haoqi; Wang, Qingling; Meng, Fanxue; Ren, Xiang (Frontiers in Earth Science, 2023)
We present new LA-ICP-MS detrital zircon U-Pb age and trace element data of the Late Mesozoic sedimentary sequences from the western Shandong and Tanlu fault zone, with the aim to constrain the depositional ages and sedimentary sources. The samples from the western Shandong have similar U-Pb age spectra, which can be divided into three major age groups, peaking age at circa 2,475–2,540 Ma, 1820–1870 Ma and 257–285 Ma, with minor Mesoproterozoic, Neoproterozoic and Paleozoic detrital zircon grains. The sample JN recovered from the Tanlu fault zone has an overwhelming majority of the Early Cretaceous detrital zircons with the age peak at circa 125 Ma, whereas the Archean and Paleoproterozoic detrital zircons are subordinate. The weighted average age of the youngest zircons show that the Santai Formation probably had begun deposition at circa 158 Ma and terminated deposition at circa 150 Ma, and the Tianjialou Formation of the Dasheng Group had begun deposition at circa 122 Ma. Our study indicates that the activity of the dinosaurs might occur during the Late Jurassic rather than the Cretaceous in the Shandong province. In addition, most detrital zircons of the studied samples are characterized by the high Th/U ratios and left-inclined REE patterns, revealing a magmatic origin. Morphologically, most detrital zircon grains characterized by angular to sub-rounded shapes indicate a middle-short distance transport from the source regions, whereas minor detrital zircon grains show rounded shapes, indicating a long-distance transport or multiphase recycling. According to detrital age populations in this study, combined with previously published data, we conclude that depositional provenances of the Santai Formation were mainly derived from the western Shandong and Jiao-Liao Belt, and minor detritus were derived from the northern part of the North China Craton and Xing-Meng orogenic belt. The sediments deposited in the Tanlu fault zone were mainly derived from the volcanic and subvolcanic rocks of the Qingshan period in the eastern Shandong, and subordinate depositional sources were from the Jiao-Liao and the basement uplift of the western Shandong, with minor supplier being derived from the Yinshan-Yanshan orogenic belt. The detrital provenance of the Santai Formation indicates that extension of the eastern NCC occurred during the Late Jurassic. The Neoproterozoic detrital zircons play a minor role in the studied strata, indicating that the large sinistral movement of the Tanlu fault zone might have occurred at the Early-Middle Jurassic and formed a paleogeographic separation of the western Shandong and eastern Shandong (Sulu orogenic belt).